Profile of accidental injuries and poisoning in children and analysis of the predisposing factors - M. S., Meenakshi; R., Senthilprabhu (International Journal of Research in Medical Sciences, 2017)
Background: Accidents continue to be the leading cause of death and disability between 1 year and 15year age group. Trauma lurks both developed and developing nations but in different guises. The aim is to determine the epidemiology, clinical profile and outcome of children with accidental injuries and poisoning and to analyse the factors predisposing to accidents in children. Methods: This was a prospective cohort study done at Institute of Social Pediatrics, Govt. Stanley Medical College, Chennai, Tamil Nadu, India between September 2006 to August 2007. Results: Most common age group for occurrence of accident is less than 3 years n=68 (37.8%). Male children 108 (60%) outnumbered female children 72 (40%). Among the accidents falls accounted for 32.8% cases which were the commonest followed by Road Traffic Accident (RTA) 22.2%, poisoning 21.1%, Foreign body 7.8%, Burns 6.1%, Drowning 1.7 % in decreasing order of frequency. In and around Home n=114 (63.3%) was the commonest place of occurrence of accident followed by 26.7% in streets, 3.9% in schools and 3.3% in playground. Sunday contributes to more accidents (20%) than any other day. Accidents were common between 3PM to 6 PM (36.1%). Among RTA and fall, skeletal injuries accounted for 49.9% followed by head injury 27.4%, and soft tissue injuries 25.6%. Among burns, the most common site involved was limbs and deep burns were more common than superficial burns. 86.7% of cases recovered completely, 5% had permanent residual deformity and death in 1.1% of cases. The various social factors were analyzed as risk factors for accidents using multivariate logistic regression analysis and was found that nuclear family had ODD’s ratio of 2.232 (95% C.I 1.004 -4.961), age of the mother <25years with ODD’s ratio 1.252 (95% C.I 1.085-3.025) and socio-economic class III and IV together with ODD’s ratio 1.603 (95% C.I 1.064 - 3.379). Conclusions: Accidents and poisoning lead to significant morbidity in children in this study. Comprehensive prevention strategies need to be implemented to bring down the rate of accidents.